Analysis of android-based game learning media needs on elementary thematic learning - Murtiningsih Murtiningsih; Darsinah Darsinah; Murfiah Dewi Wulandari; Minsih Minsih; Yeny Prastiwi (Universitas Negeri Yogyakarta, 2022)
This study aimed at identifying the need of android-based game learning media as an elementary thematic learning medium. This is qualitative research with an R D (Research and Development) approach. The the ADDIE model was also used at the analysis stage. The samples of the study were 3 teachers and 37 students of 6th grade in Wonogiri elementary school. The sample was chosen using purposive sampling method. The data collection techniques were carried out using questionnaires and semi structured interviews. The data then analyzed using percentage system and then narrated descriptively. The results of this study show that there is a need for android-based game-based learning development as an elementary thematic learning medium, especially 6th grade students. Some development also needs to be done to be customizable to particular criteria and specifications. The development of game-based learning media with various applications and multimedia will be able to produce learning innovations, which ultimately realize a quality learning process in the classroom, so that learning goals can be achieved.